Zwischen Karten Alexander von Humboldts "Atlas géographique et physique des régions équinoxiales du Nouveau Continent" - Buchholz, Amrei 1982- (Ars et Scientia, 2020)
After returning from his American research expedition, Alexander von Humboldt worked on an atlas of the "New Continent," the Atlas géographique et physique des régions équinoxiales du Nouveau Continent. The thirty-nine maps in the atlas provide information about the genesis of the Earth and the interaction of the forces of nature as well as the cultural-historical development of geographic knowledge itself. Amrei Buchholz describes the conception and production of the atlas for the first time. She shows that Humboldt’s presentation of knowledge, which has hitherto not been addressed by the research, is exemplary for the practice of mediating knowledge visually around 1800, in which heterogeneous types and topics of presentation were brought together heuristically.